Postpartum Health Care Utilization at an Academic Center and Affiliated Community Health Centers [19M]. (May 2016) - Blake-Lamb, Tiffany; Hatoum, Ida; Kotelchuck, Milt; Bryant, Allison
Abstract : INTRODUCTION: Optimizing women's health after pregnancy holds potential to beneficially impact subsequent pregnancy outcomes. We compare postpartum care utilization for women at an academic medical center and affiliated community health centers. METHODS: Administrative encounter data were examined for women who received prenatal care and delivered from 2006–2010 to identify health care encounters within 2 months after delivery, and among women who enrolled in hospital-affiliated primary care practices prior to delivery to examine utilization in the 2 years after delivery. Univariate and multivariate models were built to identify predictors of care utilization. RESULTS: Among 8, 749 and 4, 439 women receiving prenatal care at the academic center and affiliated health centers, respectively, most returned for an obstetric postpartum visit (86% vs 79%, P <.0001), and additionally some had encounters with primary care (7% vs 12%, P <.0001), other outpatient clinics (13% vs 14%, P =.094), the emergency department (2% vs 3%, P <.0001), or hospital admissions (1.7% vs 1.9%, P =.41) during the initial 2 months postpartum. Among the 3, 743 and 2, 034 women with previously established primary care, the majority sought primary care (79% vs. 84%, P <.0001) and other outpatient services (71% vs 74%, P =.019) in the 2 years after delivery—with increasing age, having a chronic health condition, and accessing care at a community health center increasing the odds of utilizing postpartum primary care. CONCLUSION: After pregnancy most women utilize the obstetric postpartum visit and primary care, emphasizing the opportunity to optimize preconception health care at these encounters. A community-based care delivery model may facilitate primary care utilization after pregnancy.